Modeling transient vibration-sound generation processes - Lukianov, Petro Volodymyrovich (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2020)
In this paper, a problem of sound generation of two-blade rotor sinusoidal shape during helicopter landing is solved. Near and far sound field characteristics have been calculated. A comparative analysis of obtained numerical results with results for Mach number 0.2<M<0.4 is given. In particular noticed, that for a low Mach’s number M<0.1 transitional mode can occurs, which produces a blade flutter as a result.